Obraz Aleksandra Kołczaka i wojny domowej w Rosji, przedstawiony w filmie "Admirał", a współczesna rosyjska świadomość historyczna - Jędraszczyk, Katarzyna; Rabinowicz, Władimir (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2015)
The Image of Alexander Kolchak and the Civil War of 1917 in Admiral, and contemporary Russian Historical Consciousness The article offers an analysis of the image of Alexander Kolchak in Russian cinematography. The most extensive portrayal of both this figure and of the Russian civil war is found in the film Admiral. Contemporary Russian historical consciousness has been modified or moulded by images conveyed in films. Historical cinema is an effective means by which attitudes to the past can are formed and may be used as a tool in carrying out historical politics.